Development of whey-fruit-based energy drink premixes - Patil, Shital; Sahoo, A K; Patil, N J; Lokhande, S M; Ranveer, R C (Journal of Postharvest Technology, 2019)
Moment vitality powder by utilizing Spray drying strategy is later, straightforward, monetary and beneficial technique. The readied watermelon juice and protenious whey with caffeine added substances gives moment incitement which gives better quality item. The emulsion for splash drying was set up by 60:40 watermelon and concentrated whey with 10% sugar, 75 mg of caffeine and 0.50 mg of CMC which was advanced based on Sensory Analysis. The readied emulsion was blended with various convergence of Malto-dextrin powder as emulsifying operator which impact on the profitability of the last premix. 5% maltodextrin powder gives most extreme yield when contrasted with 3% maltodextrin. 75 mg of caffeine gives impeccable incitement and concentrated whey give greatest protein substance to premix. The last premix was pressed into metalized film which increment the sensorial and microbial security of the item. Dampness content and disintegration time increments though water movement and mass thickness diminishes amid the multi month of capacity. At long last outcome gives the better quality, low water action, less demanding transport and capacity premix was readied.